Komunikasi Pemasaran Produk Kasur di Media Sosial Tiktok - Aryana Nurwigati; Yenni Yuniati (Bandung Conference Series: Public Relations, 2023)
A Abstract. The development of technology and information that occurs in the present makes a lot of changes. In today's society, it is very easy to do activities without having to meet directly or face-to-face. One of the proofs that occur from the development of technology and information is in marketing activities. Social media is a new media that provides facilities to carry out all activities anytime and anywhere, so that social media becomes a platform used to carry out marketing activities. Marketing communication is a very important aspect in the success of economic activities, one of which is in marketing activities. The purpose of this research is to determine the application of marketing communications carried out by the INTHEBOX brand on TikTok social media, through the use of the Live Streaming feature in the TikTok application. This research uses qualitative methodology case study approach with IMC (Integrated Marketing Communication) theory. This research collecting data by observation, interviews and documentation. Abstrak. Perkembangan teknologi dan informasi yang terjadi di masa sekarang membuat banyak perubahan. Di masa sekarang masyarakat sangat mudah untuk melakukan aktivitas tanpa harus bertemu secara langsung atau tatap muka. Salah satu bukti yang terjadi dari perkembangan teknologi dan informasi yaitu pada kegiatan pemasaran. Media sosial merupakan media baru yang menyediakan fasilitas untuk melakukan segala aktivitas kapan pun dan dimana pun, sehingga media sosial menjadi sebuah media yang digunakan untuk melakukan kegiatan pemasaran. Komunikasi pemasaran menjadi aspek yang sangat penting dalam keberhasilan kegiatan ekonomi, salah satunya yaitu dalam kegiatan pemasaran. Tujuan dalam penelitian ini yaitu untuk mengetahui penerapan komunikasi pemasaran yang dilakukan brand INTHEBOX di media sosial TikTok, melalui pemanfaatan fitur Live Streaming yang ada di aplikasi TikTok. Penelitian ini menggunakan metodologi kualitatif pendekatan studi kasus dengan teori IMC (Integrated Marketing Comunication). Pengumpulan data dilakukan dengan observasi, wawancara dan dokumentasi.